The portable seminary - Horton, David (David E.) (Minneapolis, Minn. : Bethany House, 2006)
"Lay people and pastors will find the major topics included in this volume that would be found in a typical seminary master's program. The information is gleaned from a distinguished international faculty of more than fifty professors, lecturers, and authors"--Provided by publisher.
Includes bibliographical references (p. [699]-756) and index.
Keywords: Pastoral theology